1992
DOI: 10.1111/j.1530-0277.1992.tb00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Morphine and Naloxone on Ethanol‐ and Sucrose‐Reinforced Responding in Nondeprived Rats

Abstract: In the following series of experiments, effects of morphine (0.1, 0.3, 1.0, 3.0, and 10.0 mg/kg) and naloxone (0.1, 0.3, and 1.0 mg/kg) were assessed in nondeprived rats trained to leverpress with 10% ethanol, sweetened ethanol, or 5% sucrose and water as the reinforcers. Morphine, at doses of 0.1, 0.3, and 1.0 mg/kg had little effect on responding with ethanol or sweetened ethanol available on a fixed ratio 4 (FR4) schedule of reinforcement, but at the 3.0 mg/kg dose, morphine suppressed responding to near ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 35 publications
4
30
0
Order By: Relevance
“…In STUDY 1, it was found that during the maintenance phase, low doses of naltrexone and fluoxetine decrease lever presses for alcohol. These data are in agreement with previous reports which have shown that preferentially mu opioid receptor antagonists and SSRI agents, at doses similar to the ones used in the present report, decrease alcohol self-administration during the maintenance phase (e.g., Murphy et al 1988: Haraguchi et al 1990Hyytia and Sinclair 1993;Schwarz-Stevens et al 1992; see Amit et al 1991 andUlm et al 1995 …”
Section: Discussionsupporting
confidence: 94%
“…In STUDY 1, it was found that during the maintenance phase, low doses of naltrexone and fluoxetine decrease lever presses for alcohol. These data are in agreement with previous reports which have shown that preferentially mu opioid receptor antagonists and SSRI agents, at doses similar to the ones used in the present report, decrease alcohol self-administration during the maintenance phase (e.g., Murphy et al 1988: Haraguchi et al 1990Hyytia and Sinclair 1993;Schwarz-Stevens et al 1992; see Amit et al 1991 andUlm et al 1995 …”
Section: Discussionsupporting
confidence: 94%
“…Thus, opioid receptors within some (eg NACC and VTA), but not all mesolimbic substrates can selectively modulate EtOH-reinforced behaviors. Previous reports in the literature have suggested that a selectivity in reducing EtOH-motivated behaviors in rodents was difficult, equivocal, or not clearly observable (Brown and Holtzman, 1979;Herz, 1997;Schwartz-Stevens et al, 1992;Weiss and Koob, 1991;Weiss et al, 1990). However, we hypothesized that the operant contingencies under which one evaluates opiate receptor antagonists following parenteral or direct administrations into the CNS is a very important factor in observing selective antagonism on EtOH-motivated behaviors.…”
Section: Differential Dose and Reinforcer 'Sensitivity' Exist In The mentioning
confidence: 89%
“…The exact neurobiological substrate(s) participating in EtOH's rewarding effects, however, are not well understood, in part because the majority of the preclinical studies using opioid antagonists have been conducted using systemic drug injections (Froehlich and Li, 1993;Herz, 1997;Reid and Hubbell, 1992;Schwartz-Stevens et al, 1992). While it has been assumed that the action of opioid antagonists on EtOH's reinforcing properties are mediated centrally (McBride and Li, 1998), this has only been documented in a few published reports in the literature (Heyser et al, 1999;Hyytiä and Kiianmaa, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, pretreatment with these opioid receptor antagonists did not eliminate initiation of alcohol drinking or "alcohol sampling" (Hyytia & Kiianmaa, 2001;Schwarz-Stevens, Files, & Samson, 1992;Siviy, Calcagnetti, & Reid, 1982;Stromberg, Mackler, Volpicelli, & O'Brien, 2001). It should be noted, however, that animal and human studies differ with regard to several important factors.…”
Section: Maintenance Of Abstinencementioning
confidence: 97%